Line Profiles of Forbidden Emission Lines and What They Can Tell Us About Protoplanetary Disk Winds - A. Nemer; J. Goodman (The Astrophysical Journal, 2024)
Emission in forbidden lines of oxygen, neon, and other species are commonly used to trace winds from protoplanetary disks. Using Cloudy, we calculate such emission for parametrized wind models of the magnetothermal type, following Bai et al. These models share characteristics with both photoevaporative and magnetocentrifugal winds, which can be regarded as end members, and are favored by recent theoretical research. Both broad and narrow low-velocity components of the lines can be produced with plausible wind parameters, something that traditional wind models have difficulty with. Line luminosities, blueshifts, and widths, as well as trends of these with accretion luminosity and disk inclination, are in general accordance with observations.